IMPLEMENTASI CLOUD COMPUTING MENGGUNAKAN AWS ELASTIC CLOUD COMPUTE UNTUK PEMETAAN TEMPAT WISATA - Sukron Hadi Maulana (Universitas Lambung Mangkurat, 2026)
Lombok Island is one of Indonesia's leading tourist destinations. West Lombok offers numerous natural attractions, including beaches, rivers, waterfalls, and more, for tourists to choose from. However, tourists often search for information about a destination online using smartphones. Search engines like Google Maps only display the location without providing a description or explanation of the tourist attraction's history. Therefore, this study will discuss the development of a tourism mapping website using cloud computing, utilizing Amazon Web Services. Some of the services used include Elastic Compute Cloud (EC2) as a web server, S3 Bucket as data storage, IAM Users as service access and security, and Relational Database Service (RDS) as the database system. The website will be developed using the Software Development Life Cycle (SDLC) methodology, which includes analysis, design, implementation, testing, and maintenance to ensure a structured and reliable system. An additional layer of security, the Snort Intrusion Detection System (IDS), will be implemented to detect potential attacks and track suspicious activity. So, this website is expected to be able to provide more interactive information in a safe and stable manner.